Innovation Of A Holistic And Integrated Approach To Improve - Yuly Peristiowati; Hariyono; Zauhani Kusnul3 (Journal of Health Science Community, 2025)
Diabetic neuropathy is a serious complication of diabetes mellitus that can lead to a decline in patients' quality of life. This study aimed to evaluate the effectiveness of various approaches to diabetic neuropathy care, including nutrition, digital technology, clinical simulation, and traditional protocols. A systematic literature review (SLR) was used, analyzing six primary articles published between 2015 and 2025. The results showed that nutritional approaches such as Metanx can significantly reduce neuropathy symptoms and improve patients' quality of life. Digital technology approaches have also been shown to improve patients' self-efficacy and self-care behaviors, while virtual simulation can improve nurses' clinical skills. The conclusion of this study is that a more holistic and integrated approach is needed to improve the quality of life of diabetic neuropathy patients. Future research should include a more robust study design with an adequate control group to ensure the validity of the findings .